Blood : the science, medicine, and mythology of menstruation - Gunter, Jen (Citadel Press, Kensington Publishing Corp., 2024)
The New York Times best-selling author of The Vagina Bible offers empowering, period-positive, no-nonsense facts about the science, medicine and myths surrounding menstruation.